Admission serum potassium level is associated with in-hospital and long-term mortality in ST-elevation myocardial infarction - (:unkn) unknown (My University, 2016)
0

Objective: Current guidelines recommend a serum potassium (sK) level of 4.0-5.0 mmol/L in acute myocardial infarction patients. Recent trials have demonstrated an increased mortality rate with an sK level of >4.5 mmol/L. The aim of this study was to figure out the relation between admission sK level and in-hospital and long-term mortality and ventricular arrhythmias.Methods: Retrospectively, 611 patients with ST-elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention were recruited. Admission sK levels were categorized accordingly: <3.5, 3.5-<4, 4-<4.5, 4.5-<5, and >=5 mmol/L.Results: The lowest in-hospital and long-term mortality occurred in patients with sK levels of 3.5 to <4 mmol/L. The long-term mortality risk increased for admission sK levels of >4.5 mmol/L [odds ratio (OR), 1.58; 95% confidence interval (CI) 0.42-5.9 and OR, 2.27; 95% CI 0.44-11.5 for sK levels of 4.5-<5 mmol/L and >=5 mmol/L, respectively]. At sK levels <3 mmol/L and >=5 mmol/L, the incidence of ventricular arrhythmias was higher (p=0.019).Conclusion: Admission sK level of >4.5 mmol/L was associated with increased long-term mortality in STEMI. A significant relation was found between sK level of <3 mmol/L and >=5 mmol/L and ventricular arrhythmias
Keywords: Kalp ve Kalp Damar Sistemi